Alternative actuation methods of a BorgWarner eTVD system - Houshangi,Milad (2025)
This master’s thesis investigates the feasibility of alternative actuation methods for the BorgWarner electric Torque Vectoring with Disconnect (eTVD) system. Currently employed in several car models, the existing eTVD system performs admirably. However, BorgWarner’s commitment to technological improvement and the desire to attract potential customers to this unique technique serve as the impetus for this research. The primary focus lies in achieving faster response times without compromising system size or weight. Additionally, cost considerations play a pivotal role in this investigation. In this study, a comprehensive requirement specification was meticulously compiled. Subsequently, an iterative product development approach was employed to devise a solution. To gain a thorough understanding of existing concepts, an in-depth analysis of current and similar products was conducted. The most promising concepts were rigorously benchmarked against one another, employing calculations, Amesim simulations, and critical reasoning to evaluate their functional efficacy.